The Role of English Language in Fostering Human Development in Nigeria - P, Phineas T.; I, Yusuf L.; F, Ahmed F.; G, Dauda (Lembaga Yasin AlSys, 2025)
The language policy in Nigeria granted the English language as the status of being the sole official language, and the language of instruction in the country. This approach influenced the educated people's competence, and subsequently, attitudes towards others within their locality and global arena. The study aims to investigate the Role of English language in fostering human development in Nigeria. This paper argues that English as the Nigerian official language is well accepted due to the multi-lingual state of Nigeria. The study observes that English language is a political and social element in the process of building, unification, and maintaining the Nigerian state and as an essential element of national development. This study contributes to the understanding of multi-lingual nations and supports the research literature which showed that English language plays a significant role in unifying multi-lingual Nigeria. English language has the status of being the sole official language in Nigeria, and the language of instruction in the country. Its role in fostering socio-economic development cannot be overemphasized. The study also examined the role of the English Language in the socio-economic Development of Nigeria. The study observed that English language is a political and social element in the process of the socio-economic development of the Nigerian state and as an essential element of national development. This paper also recommends that grassroots language education should be given to all citizens. This, in turn, will help promote human capacity building and the socioeconomic development of Nigeria.